Entre tinta y rebeldía: contracultura literaria en El Corno Emplumado 1962-1969 - Esquivel Torres, Jorge Luis (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
The magazine El Corno Emplumado was published in Mexico and had an international distribution from 1962 to 1969. Various artists and writers participated in its pages, including those linked to the countercultural scene in different parts of the world. The publication reflected dissent both internationally and locally, weaving a mosaic of artistic and literary expressions gathered throughout its pages. The editors, Margaret Randall and Sergio Mondragón, promoted the project with the intention of building a cultural bridge that would break national borders, so it was edited in a bilingual format: Spanish and English. The magazine served as a literary response to the events of the Cold War. In addition, it played a crucial role in networking among counter-cultural writers internationally. Throughout its seven years of production, El Corno Emplumado reached a wide diffusion, evidencing the dissent towards the dominant systems established in the 1960s. The project came to an end due to government censorship and surveillance, particularly through Mexican government intelligence agencies such as La Dirección Federal de Seguridad. The purpose of this research is to analyze the literary dissidents that emerged during that decade and that collaborated in the pages of the magazine, with the intention of exploring the cultural networks, political and social circles that surrounded the magazine and its editors under a gaze of international literary and counter-cultural connection.

La revista El Corno Emplumado fue editada en México y tuvo una distribución internacional desde 1962 hasta 1969. En sus páginas participaron diversos artistas y escritores, incluyendo aquellos vinculados a la escena contracultural en diferentes partes del mundo. La publicación reflejó la disidencia tanto a nivel internacional como local, tejiendo un mosaico de expresiones artísticas y literarias reunidas a lo largo de sus páginas. Los editores, Margaret Randall y Sergio Mondragón, impulsaron el proyecto con la intención de construir un puente cultural que rompiera las fronteras nacionales, por lo que fue editada en un formato bilingüe: español e inglés. La revista funcionó como contestación literaria a los acontecimientos de la Guerra Fría. Además, desempeñó un papel crucial para la formación de redes entre escritores contraculturales a nivel internacional. A lo largo de sus siete años de producción, El Corno Emplumado alcanzó una amplia difusión, evidenciando la disidencia hacia los sistemas dominantes establecidos en la década de 1960. El proyecto llegó a su fin debido a la censura y vigilancia gubernamental, particularmente a través de organismos de inteligencia del gobierno mexicano como la Dirección Federal de Seguridad. El propósito de esta investigación es analizar las disidencias literarias que surgieron durante esa década y que colaboraron en las páginas de la revista, con la intención de explorar los entramados culturales, políticos y sociales que rodearon a la revista y a sus editores bajo una mirada de conexión internacional literaria y contracultural.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-R-M-2024-0237; Historia de América; Literatura contracultural; Guerra Fría; Vigilancia política; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18596